A Targeted Literature Review of the Disease Burden in Patients With Symptomatic Peripheral Artery Disease. (April 2020) - Bauersachs, Rupert; Debus, Sebastian; Nehler, Mark; Huelsebeck, Maria; Balradj, Janita; Bowrin, Kevin; Briere, Jean-Baptiste
Patients with peripheral artery disease (PAD) have an increased risk of cardiovascular (CV) and limb events, but the disease is frequently underdiagnosed and treatment options are limited. This review examines the disease burden of symptomatic PAD as well as key guideline recommendations. Publications were identified using the ProQuest portal to access the Medline, Medline In-Process, and Embase databases. Search terms for symptomatic PAD were combined with terms relevant to epidemiology, burden, treatment practice, and physiopathology. Articles in English published between January 2001 and September 2016 were screened according to the population, interventions, comparator, outcomes, and study design criteria. Relevant publications (n = 200) were identified. The reported incidence and prevalence of PAD varied depending on the definitions used and the study populations. Patients generally had a poor prognosis, with an increased risk of mortality, CV, and limb events and decreased quality of life. Guideline recommendations included ankle–brachial index measurements, exercise testing, and angiography for diagnosis and risk factor modification, antiplatelets, cilostazol, exercise therapy, or surgical interventions for treatment, depending on the patient profile. The clinical, humanistic, and economic burden of disease in patients with symptomatic PAD is substantial and needs to be reduced through improved PAD management.